MANUFACTURING AND TESTING OF DATE PALM VIBRATION MOTORIZED FRONDS CUTTER - & et al., Abbood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The objective of this study was manufacturing and testing a vibration motorized date palm fronds cutter equipment used to pruning date palm tree, this equipment is man back handling and easily used for cut date fronts base. Gasoline two stroke engine which handle on worker’s back was used to provide a vibration movement for sharp blade to cut the fronds, machine consists of many parts includes engine, flexible shaft, fixed shaft, gear case and knife. Three knives cutting angle were used in this research. Frond cutting time ,one palm tree pruning (three rows of fronds) vibration of cutting level ,noising level and productivity were measured in this study .Randomized complete block design with three replications was used in the experiment. Least significant differences (L.S.D) under 0.05 level of probability was used to compare the means of treatments . Results showed that 45° cutting angle was superior in obtaining the lowest time of one frond cutting stood 4.30 second, the lowest variation of surface cutting level stood 5.07 mm and highest productivity reached 7.27 tree.h-1 . Results also showed that there was no significant differences in noise level attributed to cutting angle. Manufacturing date palm pruning mechanical cutter equipment was successfully done at 45° cutting angle with acceptable noise level, vibration and high field productivity .